2023
DOI: 10.3389/fpubh.2022.1015138
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep duration and myopia among Chinese children during the COVID-19 pandemic: A cross-sectional study

Abstract: BackgroundThe studies on the association between sleep duration and myopia are limited, and the evidence is inconsistent. This study aimed to evaluate the association between sleep duration and myopia, cycloplegic spherical equivalent (SE) and axial length (AL) among Chinese children during the Corona Virus Disease 2019 (COVID-19) pandemic.MethodsThe study was a cross-sectional study on Chinese children aged 6–18 years. The comprehensive ophthalmic examinations for children included cycloplegic SE, AL, and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…In our study, sleep duration of ≤8 hours increased the risk of fast myopia progression in children by 2.7 times. This was in line with previous study by Huang et al [32] , which revealed that children with sleep duration of more than or equal to 8 hours were less myopic and had less myopic SE in their univariate regression analysis, although after adjusting for several factors, the result was not signi cant. Studies conducted in Korea [33] and Japan [34] also showed that sleep duration was negatively associated with myopia.…”
Section: Sleep Duration and Its Impact On Myopia Progressionsupporting
confidence: 92%
“…In our study, sleep duration of ≤8 hours increased the risk of fast myopia progression in children by 2.7 times. This was in line with previous study by Huang et al [32] , which revealed that children with sleep duration of more than or equal to 8 hours were less myopic and had less myopic SE in their univariate regression analysis, although after adjusting for several factors, the result was not signi cant. Studies conducted in Korea [33] and Japan [34] also showed that sleep duration was negatively associated with myopia.…”
Section: Sleep Duration and Its Impact On Myopia Progressionsupporting
confidence: 92%
“…A Singaporean study found no independent association between sleep duration and myopia in primary school students [12]. This nding was also supported by other Chinese study aimed at school-aged children [13,14]. Jee et.…”
Section: Basic Characteristicssupporting
confidence: 55%
“…In contrast, however, Li et al ( 15 ), in a cross-sectional study, did not find an association between sleep quality, duration and myopia in primary school children from Singapore. Huang et al ( 17 ) reported the relationship between sleep duration and myopia in Chinese children during the COVID-19 Epidemic, and a total of 1,140 children were included in the analysis, which showed that sleep duration was not associated with myopia after adjusting for age, gender, parental myopia, outdoor hours, and hours of continuous uninterrupted near work. The dose–response results of this survey indicated a non-linear relationship between sleep duration and the risk of myopia, with a threshold point of 8 h. The results of the multivariate logistic regression analysis ultimately showed that sleep duration below 8 h was associated with an increased risk of myopia.…”
Section: Discussionmentioning
confidence: 99%